La profesionalización docente, desde la dimensión pedagógica. Una estrategia para la gestión de la calidad universitaria. - Rivero, Élida; Busto, Cúmanda; Zúñiga, Gladys; Carmenate, Luis (My University, 2019)
Professionalization as a process is a demand that comes from social development and as a trend it is desirable because it guarantees greater quality in the teaching performance. For the university professor, this process converges in two dimensions: that of teacher and that of researcher. Objective: The present work seeks to manage a strategy of professionalization from the pedagogical dimensions that contributes to the consolidation of professional performance and consequently improves the quality of the training process in which it develops. Methodology: The essential aspects were evaluated if the professionalization of the university teacher is to be achieved. Assuming the notion that this does not have initial pedagogical training. Practicing the profession first by imitation and then by accumulation of knowledge and experiences, which allows it to reach levels of performance that, while ensuring a certain success in the delivery of their subject, will not be a sufficient condition to resize the process of training professionals of the 21st century. Conclusion: Given this, the direct relationship between the improvement in the quality of higher education and a process of professionalization that allows the teacher to make sound decisions about the changes that must be introduced in their performance as manager of the training process is corroborated.
La profesionalización como proceso es una exigencia que deviene del desarrollo social y como tendencia es deseable porque garantiza mayor calidad en el desempeño docente. Para el profesor universitario este proceso converge en dos dimensiones: el de docente y el de investigador. Objetivo: El presente trabajo busca gestionar una estrategia de profesionalización desde las dimensiones pedagógicas que contribuya a la consolidación del desempeño profesional y consecuentemente mejore la calidad del proceso formativo en que se desarrolla. Metodología: Se evaluaron los aspectos esenciales si se aspira a lograr la profesionalización del docente universitario. Asumiendo la noción de que este no posee formación pedagógica inicial. Ejerciendo la profesión primero por imitación y luego por acumulación de saberes y experiencias, lo que le permite alcanzar niveles de desempeño que, si bien aseguran un determinado éxito en la impartición de su asignatura, no serán condición suficiente para redimensionar el proceso de formación de los profesionales del siglo XXI. Conclusión: Ante esto, se corrobora la relación directa entre la mejora en la calidad de la educación superior y un proceso de profesionalización que permita al docente tomar decisiones acertadas sobre los cambios que debe introducir en su actuación como gestor del proceso formativo.
Keywords: Rivero; Élida; Busto; Cúmanda; Zúñiga; Gladys; Carmenate; Luis